2021
DOI: 10.1186/s13048-021-00766-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi-gene-based immune prognostic signature in ovarian Cancer

Abstract: Background Various components of the immune system play a critical role in the prognosis and treatment response in ovarian cancer (OC). Immunotherapy has been recognized as a hallmark of cancer but the effect is contradictional. Reliable immune gene-based prognostic biomarkers or regulatory factors are necessary to be systematically explored to develop an individualized prediction signature. Methods This study systematically explored the gene expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Here, the three subtypes identified showed significant differences in immune score, and the highest immune score was recorded in C1. We anticipated that C1 was the highest risk score subtype, which was in corroboration with previous findings indicating that higher risk score subtypes are correlated with higher immune score ( 32 34 ). This observation was further supported by the increase of immune cells in C1 subtype compared to C2 and C3.…”
Section: Discussionsupporting
confidence: 90%
“…Here, the three subtypes identified showed significant differences in immune score, and the highest immune score was recorded in C1. We anticipated that C1 was the highest risk score subtype, which was in corroboration with previous findings indicating that higher risk score subtypes are correlated with higher immune score ( 32 34 ). This observation was further supported by the increase of immune cells in C1 subtype compared to C2 and C3.…”
Section: Discussionsupporting
confidence: 90%
“…The final results showed that our signature and three other prognostic signatures, namely, a 21 immune‐related gene signature, 35 17 immune‐related gene signature 36 and 17 TF‐related gene signature 37 performed better than the other hallmark signatures in the prediction of OS in patients with OV. 11 , 35 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 Additionally, Yu et al has constructed a five GRG signature (ANGPTL4, PYGB, ISG20, SEH1L and IRS2) for patients with OV. 62 The AUCs of the signature in Yu's study at 5‐years were 0.680.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, the AUCs of the signatures at 3, and 5 years were 0.709, 0.762, respectively, which were significantly higher than those of most hallmark predictive models. Table 4 shows that the AUCs of the other three prognostic signatures, namely, the 21 immune‐related gene signature, 35 17 immune‐related gene signature (0.754 at 3 years, 0.824 at 5 years) 36 and 17 transcription factor ‐related gene signature (0.803 at 5 years), 37 were comparable to the predictive capabilities of our predictive model and distinctly higher than those of other signatures, such as the epithelial‐mesenchymal transition related gene signature, 38 TME‐related gene signature, 39 , 40 RNA‐binding protein‐related gene signature, 41 energy metabolism‐related gene signature, 42 autophagy‐related gene signature, 43 , 44 ferroptosis‐related gene signature, 45 protein‐coding gene signature, 46 and DNA methylated gene signatures. 47 The larger the AUC value of a biomarker, the better was the predictive ability of the signature, indicating that our gene signature outperformed most of the other signatures in predicting OV prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations